CONTRASTIVE LINGUISTICS AND CULTURAL LINGUISTICS - Mamatov Sardor Gayrat ogli; Abduraxmanova Zilola Yoqubjon qizi (Ustozlar uchun, 2023)
Annotation This article provides a comparison between contrastive linguistics and cultural linguistics, highlighting their differences in terms of focus, aims, methodology, and scope.Contrastive linguistics is concerned with comparing different languages to identify similarities and differences in their structure, aiding language learning and translation. In contrast, cultural linguistics explores the relationship between language and culture, emphasizing how language reflects and shapes cultural practices, values, and meanings.The methodologies used in contrastive linguistics involve formal linguistic analysis and comparative techniques, while cultural linguistics utilizes qualitative and quantitative approaches, discourse analysis, ethnography, and sociolinguistic methods to investigate the cultural nuances embedded within language.